2013
DOI: 10.1002/alr.21134
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of antibiotic‐resistant biofilms in a maxillary sinus model

Abstract: Background Chronic rhinosinusitis (CRS) is one of the most common chronic conditions in the United States. There is a significant subpopulation of CRS patients who remain resistant to cure despite rigorous treatment regimens including surgery, allergy therapy and prolonged antibiotic therapy. Antimicrobial photodynamic therapy (aPDT) is a non-invasive non-antibiotic broad spectrum antimicrobial treatment. Our previous in vitro studies demonstrated that aPDT reduced CRS polymicrobial planktonic bacteria and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 20 publications
(21 reference statements)
0
24
0
2
Order By: Relevance
“…In 2011, they described impressive in‐vitro results showing a reduction of >99.9% of CRS polymicrobial biofilm after a single PDT treatment . Their subsequent studies demonstrated safety of PDT treatment on a living human ciliated respiratory mucosal model, and effectiveness in a maxillary sinus model, matching previous results, with a reduction of the CRS polymicrobial biofilms of P aeruginosa and MRSA by >99.99% after a single treatment with a methylene blue/ethylene‐diamine tetraacetic acid (EDTA) photosensitizer and 670‐nm nonthermal activating light …”
Section: Resultsmentioning
confidence: 58%
“…In 2011, they described impressive in‐vitro results showing a reduction of >99.9% of CRS polymicrobial biofilm after a single PDT treatment . Their subsequent studies demonstrated safety of PDT treatment on a living human ciliated respiratory mucosal model, and effectiveness in a maxillary sinus model, matching previous results, with a reduction of the CRS polymicrobial biofilms of P aeruginosa and MRSA by >99.99% after a single treatment with a methylene blue/ethylene‐diamine tetraacetic acid (EDTA) photosensitizer and 670‐nm nonthermal activating light …”
Section: Resultsmentioning
confidence: 58%
“…Once activated by laser light, these dyes induce photodamage to inner organelles and promote apoptosis. In a silicone model of the human maxillary sinus inoculated with MRSA and antibiotic resistant P. aeruginosa , Biel et al demonstrated a greater than 99.9% reduction of biofilms grown from each species after a single treatment of aPDT [80]. aDPT has also demonstrated efficacy in preventing surgical site infections when used in pre-operative decolonization therapy in conjunction with chlorhexidine body wipes, in the treatment of chronic periodontitis, and in reducing biofilm formation on orthopedic prosthetic devices [8183].…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…Signifi cant preclinical studies have been performed demonstrating the safety and effectiveness of methylene blue and 670 nm aPDT (Sinuwave Inc., Bothell, WA) for treatment of CRS (Biel et al 2011a ;Biel et al 2012 ;Biel et al 2013 ). Osaki described the regression of polypoid rhinosinusitis in a dog after benzporphyrin derivative PDT with control of disease at 10 months (Osaki et al 2012 ).…”
Section: Rhinosinusitis -Antibacterial Biofi Lm Pdtmentioning
confidence: 99%